Dexmedetomidine, an alpha 2A receptor agonist, triggers seizures unilaterally in GAERS during the pre-epileptic phase: does the onset of spike-and-wave discharges occur in a focal manner? - Yavuz, Melis; İyiköşker, Pelin and Mutlu, Nursima and Kiliçparlar, Serra and Şalci, Öykü Hazal and Dolu, Gökçen and Kaymakçilar, Elif Nur and Akkol, Serdar and Onat, Filiz (Frontiers in Neurology, 2023)
Introduction The genetic absence epilepsy rat from Strasbourg (GAERS) is a rat model for infantile absence epilepsy with spike-and-wave discharges (SWDs). This study aimed to investigate the potential of alpha 2A agonism to induce seizures during the pre-epileptic period in GAERS rats. Methods Stereotaxic surgery was performed on male pups and adult GAERS rats to implant recording electrodes in the frontoparietal cortices (right/left) under anesthesia (PN23–26). Following the recovery period, pup GAERS rats were subjected to electroencephalography (EEG) recordings for 2 h. Before the injections, pup epileptiform activity was examined using baseline EEG data. Dexmedetomidine was acutely administered at 0.6 mg/kg to pup GAERS rats 2–3 days after the surgery and once during the post-natal (PN) days 25–29. Epileptiform activities before injections triggered unilateral SWDs and induced sleep durations, and power spectral density was evaluated based on EEG traces. Results The most prominent finding of this study is that unilateral SWD-like activities were induced in 47% of the animals with the intraperitoneal dexmedetomidine injection. The baseline EEGs of pup GAERS rats had no SWDs as expected since they are in the pre-epileptic period but showed low-amplitude non-rhythmic epileptiform activity. There was no difference in the duration of epileptiform activities between the basal EEG groups and DEX-injected unilateral SWD-like-exhibiting and non-SWD-like activities groups; however, the sleep duration of the unilateral SWD-like-exhibiting group was shorter. Power spectrum density (PSD) results revealed that the 1.75-Hz power in the left hemisphere peaks significantly higher than in the right. Discussion As anticipated, pup GAERS rats in the pre-epileptic stage showed no SWDs. Nevertheless, they exhibited sporadic epileptiform activities. Specifically, dexmedetomidine induced SWD-like activities solely within the left hemisphere. These observations imply that absence seizures might originate unilaterally in the left cortex due to α2AAR agonism. Additional research is necessary to explore the precise cortical focal point of this activity.